2007
DOI: 10.1007/s10096-007-0395-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of interferon-gamma in the increased tuberculosis risk in type 2 diabetes mellitus

Abstract: As patients with diabetes mellitus are at increased risk of developing tuberculosis, we hypothesized that this susceptibility to mycobacterial infection is due to a defective Th1-cytokine response. To explore this hypothesis, we examined four groups of subjects in Indonesia: 23 patients with tuberculosis, 34 patients with tuberculosis and diabetes, 32 patients with diabetes only and 36 healthy controls. Ex-vivo production of interferon (IFN)gamma, tumour necrosis factor-alpha and interleukin (IL)-1beta, 6, 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
87
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 25 publications
5
87
3
9
Order By: Relevance
“…Several early studies reported reduced proinflammatory cytokines in patients with diabetes after infection with Mycobacterium tuberculosis (3,4). Two studies, however, reported the elevation of helper T-cell type 1 (Th1) cytokines in tuberculosis-infected diabetic hosts; one was conducted in streptozocin-treated mice (5) and another in diabetic and nondiabetic patients with tuberculosis (6).…”
mentioning
confidence: 99%
“…Several early studies reported reduced proinflammatory cytokines in patients with diabetes after infection with Mycobacterium tuberculosis (3,4). Two studies, however, reported the elevation of helper T-cell type 1 (Th1) cytokines in tuberculosis-infected diabetic hosts; one was conducted in streptozocin-treated mice (5) and another in diabetic and nondiabetic patients with tuberculosis (6).…”
mentioning
confidence: 99%
“…On the other hand, many studies have found 2.1 to 8.8 times increased the risk of MDR-TB among diabetic TB patients [19,[32][33][34][35]. In addition, observational studies from Israel, Georgia, and Mexico have also shown patients with DM had a higher risk of developing MDR-TB [14,15,36].…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse and human models have demonstrated that DM alters adaptive and cell-mediated immune responses [14][15][16]. Impaired alveolar macrophage activation due to glycation of binding sites may inhibit subsequent granuloma formation in TB-DM patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse and human models have demonstrated that DM alters adaptive and cell-mediated immune responses. [18][19][20] Impaired alveolar macrophage activation due to glycation of binding sites may inhibit subsequent granuloma formation in TB-DM patients. 21 Chronic hyperglycemia may disrupt the regulation of key cytokines, such as interferon-gamma, which in turn may increase the M. tuberculosis bacterial burden and subsequent risk of death in TB-DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both mouse and human models have demonstrated that DM alters adaptive and cell-mediated immune responses. [18][19][20] Impaired alveolar macrophage activation due to glycation of binding sites may inhibit subsequent granuloma formation in TB-DM patients. …”
mentioning
confidence: 99%